Phytochemical profiling and GC-MS analysis of aqueous methanol fraction of Hibiscus asper leaves - Njoku Ugochi Olivia; Umeh Chinenyenwa Goodness; Ogugofor Martins Obinna (SpringerOpen, 2021)
Abstract Background Medicinal plants are of great importance to researchers in the field of pharmacology as most pharmaceutical industries depend on medicinal plant for their raw materials. Hibiscus asper belongs to the family Malvaceae and is well known for its medicinal properties. The present study was carried out to evaluate the antioxidant effect and possible bioactive components present in the aqueous methanol fraction of Hibiscus asper leaves. Results The phytochemical of aqueous methanol fraction of Hibiscus asper leaves (AMFHAL) revealed the presence of flavonoids, tannin, phenols, saponins, alkaloids, glycosides, terpenoids, and steroids. The GC-MS analysis revealed the presence of twenty-three bioactive compounds which include 9,12,15-octadecatrien-1-ol, n-Hexadecanoic acid, octadecatrienol acid, methyl palmitate, and phytol. Conclusion The phytochemical and GC-MS profiling of aqueous methanol fraction of Hibiscus asper leaves revealed the presence of bioactive compounds with important medicinal properties. Hence, the presence of these phytochemicals could be responsible for the therapeutic effects of the plant.